Uncertainty and commercial real estate excess returns in European markets. Issue 4 (2nd October 2022) - Lang, Elmar; Mager, Ferdinand; Hennig, Kerstin
ABSTRACT: We examine the link between uncertainty and the excess returns of direct commercial real estate markets using the well-established economic policy uncertainty index (EPU) and a novel measure of uncertainty, the world uncertainty index (WUI). Using a panel dataset of 17 European markets, we find a strong positive relation between the two uncertainty measures and excess returns in our univariate models and when we add real estate control variables. However, once macroeconomic control variables are included, only the WUI remains significant. We relate this finding to the more country-specific nature of the WUI, while the EPU potentially gives more weight to global news.